IMPLEMENTASI TEKNIK ROTOSCOPING PADA VISUALISASI ANIMASI 2D SENI BELA DIRI KARATE - Al Latif Ramadhan; Dani Arifudin; Deuis Nur Astrida (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
Rotoscoping is a 2D animation technique capable of producing accurate visualizations of human movement through frame-by-frame tracing of video references. In this study, the rotoscoping technique is applied to visualize six basic karate movements, which are characterized by dynamic motion, rhythmic patterns, and high visual precision. The aim of this research is to evaluate the effectiveness of rotoscoping in generating accurate, realistic, and efficient motion animation using the ADDIE development model. The analysis stage was carried out through observation and interviews with karate practitioners to determine the movements used as animation objects. The design stage included creating a storyboard and establishing the 2D visual style. The development stage consisted of recording the movements, trimming the footage, and converting it into an image sequence. The implementation stage involved frame elimination, key frame selection, smear frame creation, and the rotoscoping process using Clip Studio Paint. The evaluation stage was conducted through alpha testing based on three main aspects: motion accuracy, visual and aesthetic quality, and rotoscoping efficiency. The results show that most evaluation indicators were categorized as “Appropriate.” The animated movements appear natural, proportional, and consistent with the reference video. The frame elimination process successfully reduced 75%–83% of the original frames without significantly reducing motion clarity. Although minor frame rate inconsistencies were found, they did not affect the overall continuity of the animation. Therefore, the rotoscoping technique is proven effective in producing precise 2D karate animations and has strong potential for further development as a digital learning medium.